Comprehensive Physiology 2016
DOI: 10.1002/cphy.c130027
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity Stress: Bone and Connective Tissue

Abstract: The major alterations in bone and the dense connective tissues in humans and animals exposed to microgravity illustrate the dependency of these tissues' function on normal gravitational loading. Whether these alterations depend solely on the reduced mechanical loading of zero g or are compounded by fluid shifts, altered tissue blood flow, radiation exposure, and altered nutritional status is not yet well defined. Changes in the dense connective tissues and intervertebral disks are generally smaller in magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 298 publications
0
38
0
Order By: Relevance
“…Bone loss is the most recognized phenomenon related to microgravity. 7 Bone is an active organ that maintains balance of bone formation and bone resorption; in normal conditions. 8 It is considered one anisotropic material, plastic and resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Bone loss is the most recognized phenomenon related to microgravity. 7 Bone is an active organ that maintains balance of bone formation and bone resorption; in normal conditions. 8 It is considered one anisotropic material, plastic and resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Microgravity is well known to induce muscle atrophy and bone loss in astronauts [30][31][32]. A previous study suggested that microgravity-induced muscle wasting and osteopenia are partly due to enhanced bone resorption and reduced calcium absorption in the intestines [4]; however, the effects of gravity change on osteoblastic bone formation and osteoclastic bone resorption remain unclear [33].…”
Section: Muscles and Bonesmentioning
confidence: 99%
“…One pathway associated with collagen based mechanotransduction involves integrins, a family of cell surface embedded proteins that provide a link between the extracellular environment and intracellular elements [8,10]. Cells are believed to sense intrinsic mechanical properties of ECM by applying traction forces to the collagen fibers [8].…”
Section: Integrin Mediated Mechanotransductionmentioning
confidence: 99%